[Membership certificate of the Society of Engineers, Machinists, Millwrights, Smiths, and Pattern Makers]
Reproduction of colour lithograph, membership certificate of the Society of of Engineers, Machinists, Millwrights, Smiths, and Pattern Makers, depicting various landscapes and work environments of these professions Reproduction from unknown date of blank membership certificate of the Amalgamated Society of Lithographic Printers of Great Britain and Ireland; original dates from late nineteenth-century. PO-1564